In vivo imaging of vessel diameter, size, and density: A comparative study between MRI and histology. Issue 1 (16th March 2012) - Lemasson, Benjamin; Valable, Samuel; Farion, Régine; Krainik, Alexandre; Rémy, Chantal; Barbier, Emmanuel L.
Abstract The aim of this study was to compare magnetic resonance imaging (MRI) and histological estimates of the mean vessel diameter (mVD), the vessel density (Density), and the vessel size index (VSI) obtained in the same tumor‐bearing animals. Twenty‐seven rats bearing intracranial glioma (C6 or RG2) were imaged by MRI. Changes in transverse relaxations (ΔR 2*<inline-graphic xlink:href="ark:/27927/pgg1qbwk810" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and R2) were induced by the injection of an iron‐based contrast agent and were mapped using a multi gradient‐echo spin‐echo sequence. Then, brain vascular network was studied ex vivo by histology. Three regions of interest were drawn in apparently normal tissue (neocortex and striatum) and in the tumor. In vivo mVDMRI, DensityMRI, and VSIMRI were measured; ex vivo, mVDhisto, Densityhisto, and VSIhisto were quantified on the same animals. MRI and histology measurements differed by −15 to 26%. A positive correlation was found between MRI and histology for mVD, Density, and VSI counterparts (R2 = 0.62, 0.50, 0.73, respectively; P < 0.001 in all cases). This study indicates that MRI and histology yields well correlated the estimates of mVD, Density, and VSI. VSI is the closest MRI estimate to histology. As Density and mVD or VSI provide complementary information, it is worth computing them to characterize angiogenesis beyond blood volume fraction. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.